Measurement of Covalent Bond Formation in Light-Curing Hydrogels Predicts Physical Stability under Flow - Zatorski, Jonathan M.; Lee, Isabella L.; Ortiz-Cárdenas, Jennifer E.; Ellena, Jeffrey F.; Pompano, Rebecca R. (Analytical chemistry (Washington), 2024)
Photo-crosslinking hydrogels are promising for tissue engineering and regenerative medicine, but challenges in reaction monitoring often leave their optimization subject to trial and error. The stability of crosslinked gels under fluid flow, as in the case of a microfluidic device, is particularly challenging to predict, both because of obstacles inherent to solid-state macromolecular analysis that prevent accurate chemical monitoring and because stability is dependent on size of the patterned features. To solve both problems, we obtained 1H NMR spectra of cured hydrogels which were enzymatically degraded. This allowed us to take advantage of the high-resolution that solution NMR provides. This unique approach enabled the measurement of degree of cross-linking (DoC) and prediction of material stability under physiological fluid flow. We showed that NMR spectra of enzyme-digested gels successfully reported on DoC as a function of light exposure and wavelength within two classes of photo-cross-linkable hydrogels: methacryloyl-modified gelatin and a composite of thiol-modified gelatin and norbornene-terminated polyethylene glycol. This approach revealed that a threshold DoC was required for patterned features in each material to become stable and that smaller features required a higher DoC for stability. Finally, we demonstrated that DoC was predictive of the stability of architecturally complex features when photopatterning, underscoring the value of monitoring DoC when using light-reactive gels. We anticipate that the ability to quantify chemical cross-links will accelerate the design of advanced hydrogel materials for structurally demanding applications such as photopatterning and bioprinting.